The Use of Ultrasound in Bio-Treatment of Jute Yarn with Laccase Enzyme - Zolriasatein, Ali A. (Recent Innovations in Chemical Engineering, 2019)
Background and Objective: Jute fiber is highly sensitive to the action of light. Significant features of the photochemical changes lose its tensile strength and develop a yellow color. It has been proved that the phenolic structure of lignin is responsible for the yellowing of jute fiber. In order to remove lignin, jute yarns were treated with laccase enzyme in different treatment times and ultrasonic powers. Lower whiteness index and higher yellowness index values were obtained by the laccase-ultrasound system in contrast to conventional laccase treatment. Methods: The laccase enzyme which entered the fibers by applying ultrasound, decreased the tensile strength while the loss in tensile strength was lower at high ultrasound intensities. FT-IR spectrum showed that the band at 1634 cm-1 assigned to lignin completely disappeared after laccase treatment in the presence of ultrasound. The absence of this peak in the laccase-ultrasound treated jute yarn suggests complete removal of lignin. Change in the morphology of fibers was observed by SEM before and after enzymatic delignification. The laccase-ultrasound treated yarns showed a rougher surface and more porosity. On the other hand, it was more effective in fibrillation of the jute fibers than the conventional method. Finally, bio-treated jute yarns were dyed with basic and reactive dyes. Results: The results indicated that at low intensities of ultrasound and relatively long reaction times, lignin can be more effectively removed and dye strength (K/S) increased to a higher extent. Laccase-ultrasound treatment increased the color strength by 33.65% and 23.40% for reactive and basic dyes respectively. Conclusion: In the case of light fastness, the conventional laccase treated yarns provided better protection than laccase-ultrasound treated yarns.
Keywords: Jute